SCM For Monitoring Stock And Demand Online Shop Products - Nadrah Umi Kalsum; Riki Andri Yusda; Sumantri (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2026)
The rapid growth of e-commerce has increased the complexity of managing product inventory and responding to dynamic customer demand. Ineffective coordination between stock availability and demand forecasting can lead to stock shortages, overstock conditions, delayed order fulfillment, and reduced customer satisfaction. This study aims to develop and implement a Supply Chain Management (SCM) system for monitoring stock levels and demand for online shop products in real time. The proposed system integrates inventory management, demand tracking, and reporting functions to provide accurate and timely information that supports operational decision-making. The system records product inflows and outflows, monitors current stock conditions, analyzes demand trends based on transaction data, and generates informative reports to assist managers in planning procurement and replenishment activities. The implementation results demonstrate that the SCM-based monitoring system improves inventory visibility, enhances responsiveness to fluctuations in customer demand, and supports more effective stock control. Consequently, the proposed approach contributes to improving supply chain performance, minimizing inventory-related risks, and increasing the efficiency and competitiveness of online retail businesses.